AN ABILITY TO COMMUNICATE HISTORICAL EXPERIENCES OF STUDENTS IN LEARNING HISTORY SUBJECT - Asmi, Adhitya Rol (JURNAL PENDIDIKAN ILMU SOSIAL, 2017)
The development of the history education curriculum of 2013 has developed various competencies. In particular, one of those competencies is communication. Communication is the process of conveying information. In addition, good communication will support the success of student learning and also be a provision for students in the moment when they come into a community. The student's historical experience is an experience of students experienced directly by themselves in their time using a constructivist theory. Therefore, students can communicate their historical experiences either orally or in writing by drawing historical learning materials toward contemporary social issues. As a result, the students are placed as the historical actor in their age and make the history learning more meaningful.